2004
DOI: 10.1287/mksc.1030.0052
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Free Sample Promotions on Incremental Brand Sales

Abstract: The authors present a model of free sample effects and evidence from two field experiments on free samples. The model incorporates three potential effects of free samples on sales: (1) an acceleration effect, whereby consumers begin repeat purchasing of the sampled brand earlier than they otherwise would; (2) a cannibalization effect, which reduces the number of paid trial purchases of the brand; and (3) an expansion effect, which induces purchasing by consumers who would not consider buying the brand without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
114
1
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(121 citation statements)
references
References 17 publications
4
114
1
2
Order By: Relevance
“…More recently, Gedenk and Neslin (1999) and Bawa and Shoemaker (2004) analyzed the impact of free samples on subsequent (paid) purchases. The former study found that distribution of free samples increased the probability consumers would buy the brand in the future.…”
Section: Research Backgroundmentioning
confidence: 99%
“…More recently, Gedenk and Neslin (1999) and Bawa and Shoemaker (2004) analyzed the impact of free samples on subsequent (paid) purchases. The former study found that distribution of free samples increased the probability consumers would buy the brand in the future.…”
Section: Research Backgroundmentioning
confidence: 99%
“…True loyalty programs invest now for the future, commit now to the customer, and trust rather than demand trust. For example, free samples (a common up-front investment) provide future benefits such as accelerating future repeat purchases and yielding future category expansion (Bawa and Shoemaker 2004).…”
Section: Customers As Liabilitiesmentioning
confidence: 99%
“…• Prefer occasional free tickets to frequent discounted offers (Bawa and Shoemaker, 2004;Dawes, 2004).…”
Section: How To Convert Free Ticket Redemption Into Regular Paid Patmentioning
confidence: 99%